Motivation and written language in Spanish adolescents. - González-Valenzuela, María-José; Martín-Ruíz, Isaias (Anales de Psicología / Annals of Psychology, 2016)
The relationship reading and writing with cognitive-linguistic factors is analyzed for most studies, being less frequent the studies related with motivation. This study analyse the relation of the motivation and writing composition and reading comprehension, in Spanish teenagers. The sample this formed by 203 subjects of 1º (ME=12.4, DT=1.28), 2º (ME=13.6, DT=1.02) y 3º (ME=14.2, DT=1.34) of compulsory secondary education, of class media sociocultural, with normal intellectual levels and without deficits physical, psychic or sensory. The students were evaluated in motivation in terms of frequency of thoughts about performance of academics tasks. The written composition was evaluated in terms of thematic progression, semantic, morphosyntactic and metacognition. And the reading comprehension evaluated in terms of selection and organization of ideas, semantic, morphosyntactic and metacognition. The design is transversal and we realised analysis of lineal regression. The results obtained indicate that the motivation explains 17% of the written composition and between 16 and 27% of the reading comprehension, according to the academic level. The relationship of motivation and written language in this ages and their potential impact on problems in written composition and reading comprehension in adolescence is emphasized.